Comparative effectiveness of pristine and H3PO4-modified biochar in combination with bentonite to immobilize cadmium in a calcareous soil - Hamid Reza Boostani; Mahdi Najafi-Ghiri; Dariush Khalili (Scientific Reports)
Abstract Some agricultural soils are contaminated with potentially toxic elements (PTEs) like Cd, necessitating remediation to safeguard the food chain. However, a research gap exists regarding the combined use of biochar and clay minerals, particularly phosphoric acid-modified biochar and bentonite (an abundant and cost-effectiveness mineral in Iran) for Cd immobilization in contaminated calcareous soils. A 90-day factorial incubation study tested three bentonite levels (0% wt. (B0), 1% wt. (B1), 2% (B2) wt.) and five biochars treatments (control, unmodified/H3PO4-modified coffee grounds [G/GH] and municipal solid waste [M/MH], 2% wt.) for Cd immobilization in a contaminated calcareous soil. The results of analytical techniques (SEM–EDX, FTIR, sequential extraction, EDTA-desorption kinetics) indicated that the application of G biochar with bentonite (B1, B2) increased the concentration of Cd in the water-soluble and exchangeable fraction (WsEx) by 12.9% and 60.3% compared to using G biochar alone. In contrast, a synergistic effect on Cd immobilization was observed between M biochar and bentonite. The M + B2 treatment reduced EDTA-desorbed Cd by 18.7% and exhibited the slowest release rate according to the power function kinetic model. This was due to Cd transfer from bioavailable form (WsEx) to more stable fractions like iron-manganese oxides and residual forms, through increased soil pH and phosphorus levels. Overall, unmodified biochars were more effective at stabilizing soil Cd than those modified by phosphoric acid, likely due to an increase in soil pH. In conclusion, the combination of M biochar and B2 bentonite level was the most effective for Cd immobilization in contaminated calcareous soils. Long-term field-scale research with plants is needed to confirm these results.